2012
DOI: 10.1039/c1cc15992e
|View full text |Cite
|
Sign up to set email alerts
|

Porous ‘Ouzo-effect’ silica–ceria composite colloids and their application to aluminium corrosion protection

Abstract: By exploiting spontaneous emulsification to prepare porous SiO 2 particles, we report the formation of porous CeO 2 @SiO 2 hybrid colloids and their incorporation into a silica-zirconia coating to improve the corrosion protection of aluminium.The ''Ouzo effect'' is probably better known as a drinkers' conundrum than as a technique for the formation of colloidal particles. The careful addition of water to e.g. Pastis, Absinthe, etc. causes the spontaneous emulsification of a metastable droplet phase, driven by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…Either the radius of semicircles or the impedance modulus at low frequency ( e . g ., 0.1 Hz) in the Nyquist plots represents the degree of corrosion resistance originating from a sample surface; the bigger radius (or modulus) a sample exhibits, the higher corrosion resistance it has. We found that the Al film under light irradiation was more easily eroded, which was consistent with the results analyzed by absorption spectroscopy in Figure b. We further investigated the protective effect of PDA against Al corrosion using EIS.…”
Section: Resultssupporting
confidence: 81%
“…Either the radius of semicircles or the impedance modulus at low frequency ( e . g ., 0.1 Hz) in the Nyquist plots represents the degree of corrosion resistance originating from a sample surface; the bigger radius (or modulus) a sample exhibits, the higher corrosion resistance it has. We found that the Al film under light irradiation was more easily eroded, which was consistent with the results analyzed by absorption spectroscopy in Figure b. We further investigated the protective effect of PDA against Al corrosion using EIS.…”
Section: Resultssupporting
confidence: 81%
“…A spontaneous emulsication method was exploited to prepare mesoporous CeO 2 @SiO 2 hybrid particles and their incorporation into a silica-zirconia coating to improve the corrosion protection of aluminium. 40 As a synthesis method, spontaneous emulsication has the advantage of requiring neither externally applied energy nor stabilizing or templating species. To complement CeO 2 corrosion inhibition, 8-hydroxyquinoline was used, which is an effective anodic inhibitor that exhibited synergistic effects with Ce-containing compounds.…”
Section: Composite Inorganic Nanocontainersmentioning
confidence: 99%
“…We have recently shown that mesoporous silica particles (MSP) with large pore volume (≈1 mL g −1 ) and surface area (≈1000 m 2 g −1 ) can be used as nanocontainers for organic inhibitors. Employing these MSP a two times greater inhibitor uptake was achieved 18–20. The incorporation of mesoporous nanocontainers into inorganic, sol‐gel coatings improved significantly the coating corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%